Islam in Turkish Epics and their Linguistic Features - Oripov Davronbek Ravshan ugli (Scientific Trends, 2023)
This article describes the influence of Islam on the “Oguz-name” and “Kitabi dadam Qorqud”, which are considered Turkic-Oguz book epics. It is noteworthy that these works clearly trace scenes from the life of the prophets, narratives, details of the Islamic religion. In the article, the researcher, approaching from a religious point of view, puts forward and tries to substantiate the idea that, in fact, all the genesis, concepts and principles are rooted in religion. In this article, to substantiate the author’s point of view, quotes, excerpts from the holy book of Muslims “The Quran”, “Islamic history” by Sheikh Muhammad Sadiq Muhammad Yusuf (the first book) and the original text of the Turkic-Oguz book epics are given.
Keywords: Islam, “Quran”, Turkic-Oguz book epics, prophets, “Oguz-Name”, prototype, flood of Noah, Dada Qorqud, Oguz Khan.